Efektivitas Model Pembelajaran Berbasis Literasi Motorik dalam Meningkatkan Motivasi dan Hasil Belajar Pjok Kelas V - Ma'ruf Fahrudin; Meirizal Usra; Wahyu Indra Bayu; Hartati; Herri Yusfi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Physical Education, Sports, and Health (PJOK) learning in elementary schools plays an important role in developing students’ motor skills and character; however, the results of the preliminary study indicate low levels of students’ motivation and learning outcomes due to the continued use of conventional instructional approaches. This study aims to examine the effect of a motor literacy–based learning model on students’ learning motivation and PJOK learning outcomes, as well as its simultaneous effect on both variables. The study employed a one-group pretest–posttest experimental design with a sample consisting of all 30 fifth-grade students of SD Negeri Talang Nyamuk. Data were collected using a PJOK learning motivation questionnaire and a volleyball underhand passing skill test that were valid and reliable. Data analysis was conducted using a paired sample t-test and repeated measures MANOVA at a significance level of 0.05. The results indicate that the implementation of the motor literacy–based learning model has a significant effect on improving students’ motivation and PJOK learning outcomes, both partially and simultaneously. Therefore, the motor literacy–based learning model is effective in enhancing the quality of PJOK learning in elementary schools. Keywords: Learning Outcomes, Motor Literacy, Motivation